The effects of combat related stress on learning in an academic environment - Shea, Kevin Peter (Kansas State University, 2010)
This qualitative case study described the incidence of stress in the lives of Army officers, and its effect on their learning experiences at the Army‘s Command and General Staff College (CGSC). It described the experiences of officers who have completed multiple combat deployments and coped with the effects of combat related stress in an academic environment. The study further illuminated a number of issues surrounding combat related stress and learning, and framed them using the words of the eleven United States Army Command and General Staff College student participants. This qualitative case study combined the interviews of the eleven students with other members of the Fort Leavenworth, Kansas Army community to include an Army psychiatrist, a Department of Army civilian psychologist, a CGSC faculty focus group, and an Army chaplain. All of the Army officers in the study are combat veterans with an average of over 23 months of combat. This case study confirmed that being in an academic environment increased the stress levels of even combat veterans. This research further confirmed levels of anger, alcohol usage, and sleeplessness among CGSC students and its effect on their learning. It identified the impact of transitions, dual enrollment, and social functioning in family settings, as well as confirming that there is still a continued stigma associated with Soldiers seeking assistance for mental health. The stigma is exacerbated by inaccurate reporting and a culture that reflects a lack of support within certain levels of the service. This study contributes to the current body of knowledge and provides additional information and insights on the effects of combat related stress on learning. Finally, this study is relevant, germane, and timely given the number of Soldiers who have been repeatedly exposed to combat operations. This exposure to combat exponentially increases the incidence of combat related stress in their lives.
Keywords: Learning; Soldiers; Combat related stress; Transitions; adult education; academic stress; Education, Adult and Continuing (0516)